Coffee Acculturation in Saudi Arabia: Diversifying Local Wisdom and Strengthening Sustainable Economy in Coffee Value Chain - Kurniawan Arif Maspul (CV. Ulil Albab Corp, 2022)
Local wisdom is a valuable heritage of society; its existence maintains the community's identity. Coffee, which is the history of the Arabs, is a priceless heritage and local wisdom of national identity in the Arabian peninsula. Saudi Arabia nevertheless maintains this local wisdom and has strengthened it as a valuable identity. However, with diversification rather than local wisdom itself, it will enrich identity references, in this case with third-wave acculturation, which has become a global trend in the coffee value chain. This paper is a qualitative descriptive which, through the literature, observations, site visits and interviews, which were analysed, concluded that the acculturation of coffee in Saudi Arabia has become more diversified and strengthens the sustainable economy in the coffee value chain from farm to cup. Moreover, it is envisioned that Saudi Coffee 2022 will be able to mitigate the coffee sustainability challenges that will arise in the next generation.